2014
DOI: 10.1371/journal.pone.0096765
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-133a Suppresses Multiple Oncogenic Membrane Receptors and Cell Invasion in Non-Small Cell Lung Carcinoma

Abstract: Non-small cell lung cancers (NSCLCs) cause high mortality worldwide, and the cancer progression can be activated by several genetic events causing receptor dysregulation, including mutation or amplification. MicroRNAs are a group of small non-coding RNA molecules that function in gene silencing and have emerged as the fine-tuning regulators during cancer progression. MiR-133a is known as a key regulator in skeletal and cardiac myogenesis, and it acts as a tumor suppressor in various cancers. This study demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 35 publications
3
71
1
3
Order By: Relevance
“…Oncogenic membrane receptors, such as IGFR1 and EGFR are upregulated in association with reduced miR133 expression in NSCLC [131] , and a similar EGFR upregulation occurs in hormonesensitive prostate cancer and in breast cancer (Tables 46). Furthermore, a marked upregulation of cyclin C, cyclin D1 and CDK4 is seen in skin melanoma tissues associated with the reduced expression miR206; whilst the BCL2 family of prosurvival molecules (Mcl1 and BCL2L2) are both strongly upregulated due to a marked decrease in miR133b levels (> 20fold) in lung carcinoma tissue [85] .…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 97%
See 1 more Smart Citation
“…Oncogenic membrane receptors, such as IGFR1 and EGFR are upregulated in association with reduced miR133 expression in NSCLC [131] , and a similar EGFR upregulation occurs in hormonesensitive prostate cancer and in breast cancer (Tables 46). Furthermore, a marked upregulation of cyclin C, cyclin D1 and CDK4 is seen in skin melanoma tissues associated with the reduced expression miR206; whilst the BCL2 family of prosurvival molecules (Mcl1 and BCL2L2) are both strongly upregulated due to a marked decrease in miR133b levels (> 20fold) in lung carcinoma tissue [85] .…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 97%
“…In the highly metastatic PDAC [135] , relative FSCN1 expression correlates with expressed HIF1α levels, suggesting the hypoxic tumor microenvironment might induce FSCN1 ex pression, contributing to invasion and metastasis. Taken together, the downregulation of the myomiRs can contribute to the deregulated overexpression of oncogenic cell factors such as FSCN1, TAGLN2, KLF4, MET (cMET), IGFR and others, each of which can potentiate dysregulation of other cell signalling pathways, enhancing oncogenesis and metastasis (Tables 46). Interestingly, the oncogenic membrane receptors, IGF1R, TGFBR1 and EGFR are upregulated in NSCLCs due to the downregulation of miR133a, whilst NSCLC patients with highly expressed levels of miR133a tend to survive longer [131] presumably because these target oncogenic proteins are less strongly expressed. In contrast, although downregulation of miR133a occurs generally in colorectal tumors, tumors with higher miR 133a levels are associated with increased metastasis, adverse clinical characteristics and poor prognosis [136] , suggesting that other cell factors contribute to these differences in outcome.…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 99%
“…miR-133a has two subtypes, including miR-133a-1 and miR-133a-2, which are located on chromosomes 18q11.2, 20q13.33 (Mitchelson & Qin 2015). Low expression of miR-133a is associated with poor prognosis and promotion of tumorigenesis in several cancers (Kawakami et al 2012, Wu et al 2012, Wang et al 2014a,b, Lai et al 2015, Mirghasemi et al 2015. Several studies have confirmed that members of the miR-183/182/96 cluster are abnormally expressed in many tumours and are closely related to human cancers.…”
Section: Small Intestine Netmentioning
confidence: 99%
“…miR-133a is a muscle-specific microRNA, so-called myomiR, which promotes muscle growth, regulating earliest differentiation of myogenic stem cells into myoblasts (24). Regarding GC carcinogenesis, it acts as a tumor-suppressor gene: the restoration of its lower expression (as occurs in GC), in fact, can inhibit cancer cell proliferation, invasion and migration (9).…”
Section: Discussionmentioning
confidence: 99%